Pengaruh Harga, Kualitas Produk, dan Kualitas Pelayanan terhadap Kepuasan Konsumen Mie Setan Prigen Pasuruan - Muazaroh, Nailahtul; Febriansah, Rizky Eka; Indayani, Lilik (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the influence of price, product quality and service quality on customer satisfaction at the Mie Satan Prigen Pasuruan Restaurant. The research method used is quantitative and the research sample uses a purposive sampling method. This research used a sample size of 100 respondents with customers who had tried and eaten at the Mie Satan Prigen Pasuruan restaurant more than 2 (two) times. The research results show that simultaneously there is a positive and significant influence between the price, product quality and service quality variables on customer satisfaction, but partially only the product quality variable has no effect on customer satisfaction at the Mie Satan Prigen Pasuruan Restaurant.